Penerapan Akulturasi Budaya Pada Desain Mesjid Agung Serang-Banten - Andiyan Andiyan; Shyabina Rahma Fasha (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2026)
Before becoming a sturdy, standing, and attractive building, every mosque must go through a construction and building process. One example is the construction of the Grand Mosque of Serang, Banten. In mosque design, Indonesian architecture often combines various cultures. In the design of the Grand Mosque of Serang, Banten, various architectural styles are integrated. The interior design of the mosque, as well as the design of the existing building, resembles the roof design of the mosque. Since the Grand Mosque of Serang, Banten, is an ancient religious building that has survived to this day, there is cultural assimilation within it. The fact that this relic dates back to ancient times indicates that the architects who designed this mosque must have been involved in this process. The Serang, Banten Grand Mosque has distinctive Javanese, Chinese, and Dutch characteristics. This mosque has strong ties to all three cultures. This study aims to determine the acculturation of the Grand Mosque of Serang, Banten. This study applies a quantitative methodology. It investigates how the elements in the architectural design of this mosque show a fusion of cultural elements originating from various religious and cultural traditions around the world, primarily Javanese, Chinese, and Dutch cultures. The researcher emphasises the importance of cultural acculturation in understanding and appreciating the complex local cultural heritage. Additionally, it highlights the harmony among various traditions and cultures within the local community. The objective of this study is to enhance our understanding of cultural acculturation in the architecture of the Serang, Banten Grand Mosque. Furthermore, it explores how these cultural elements can be applied to its architectural design.